RANCANGAN PENGGERAK MOBIL BUGGY OTOMATIS BERBASIS MIKROKONTROLER DI POLITEKNIK PENERBANGAN MEDAN - Pinem, Hezkiel Omega Putra; Wimatra, Ayub; Sibarani, Sartika M.; Cahyadi, Catra Indra (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This research aims to design an automatic buggy vehicle driver system based on the ESP32 microcontroller at Medan Aviation Polytechnic. The system is designed to enhance the operational efficiency of campus vehicles, enabling them to operate autonomously without requiring a direct driver. The ESP32 microcontroller serves as the central controller, regulating the DC motor for steering, pneumatic motors for gas and brake pedals, and a motor driver to control the current to the motors. The system's performance testing showed that the power required for the pneumatic motors (gas and brake) is 36 watts, and for the DC motor steering, it is 72 watts. Turning tests at a 90° angle and braking tests, where the braking distance was reduced by 10 cm after calibration, indicated that the system operates as expected. These tests confirmed the system's responsiveness and accuracy in automatic operation. Technical challenges in testing, such as adjusting sensor sensitivity and calibrating the pneumatic system, were addressed through repeated trials. This research contributes to the development of vehicle automation in educational settings and offers potential for further advancement, such as integrating LiDAR and GPS sensors for improved navigation accuracy. Keywords:  Automatic Buggy Vehicle Driver, Microcontroller, ESP32, Control System, Vehicle Automation Abstrak: Penelitian ini bertujuan merancang sistem penggerak mobil buggy otomatis berbasis mikrokontroler ESP32 di Politeknik Penerbangan Medan. Sistem ini dirancang untuk meningkatkan efisiensi operasional kendaraan kampus yang dapat bergerak secara otonom tanpa memerlukan pengemudi langsung. Mikrokontroler ESP32 digunakan sebagai pusat kendali, mengatur motor DC untuk setir, motor pneumatik untuk pedal gas dan rem, serta motor driver untuk mengatur arus motor. Pengujian kinerja sistem menunjukkan daya yang dibutuhkan untuk motor pneumatik gas dan rem sebesar 36 watt, serta 72 watt untuk motor DC penggerak setir. Pengujian belokan pada sudut 90° dan pengujian pengereman yang dipersingkat 10 cm setelah kalibrasi menunjukkan kinerja yang sesuai harapan. Pengujian ini mengonfirmasi responsivitas dan akurasi sistem dalam pengoperasian otomatis. Tantangan teknis dalam pengujian, seperti pengaturan sensitivitas sensor dan kalibrasi sistem pneumatik, berhasil diatasi melalui uji coba berulang. Penelitian ini memberikan kontribusi pada pengembangan otomasi kendaraan di lingkungan pendidikan dan berpotensi untuk pengembangan lebih lanjut, seperti penggunaan sensor LiDAR dan GPS untuk meningkatkan akurasi navigasi. Kata kunci: Penggerak Mobil Buggy Otomatis, Mikrokontroler, ESP32, Sistem Kendali, Otomasi Kendaraan